David Procedure for Valve-Sparing Aortic Root Replacement in a Marfan Syndrome Patient (Cardiovascular Journal, 2022)
Valve-sparing aortic root replacement (VSRR) is an established treatment method for aortic root dilatation and aortic valve insufficiency (AI). It was developed to restore the aortic valve functions in patients of aortic root aneurysms with morphologically normal aortic valve. We hereby present a case of 67 years, male, with aortic root aneurysm and severe aortic regurgitation who was treated successfully by David’s procedure for valve sparing aortic root replacement technique.Cardiovasc j 2022; 14(2): 185-190